2019
DOI: 10.1108/jices-02-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Examination of cybercrime and its effects on corporate stock value

Abstract: Purpose Cybercrime is a prevalent and serious threat to publicly traded companies. Defending company information systems from cybercrime is one of the most important aspects of technology management. Cybercrime often not only results in stolen assets and lost business but also damages a company’s reputation, which in turn may affect the company’s stock market value. This is a serious concern to company managers, financial analysts, investors and creditors. This paper aims to examine the impact of cybercrime on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…To study the special influence of a range of incidents, from corporate purchases to joint venture establishment to CEO progressions the method of 'event study' has been engaged comprehensively in the accounting, finance and information security literature (Bose & Leung, 2013;Cavusoglu et al, 2004;Hovav et al, 2017;Kannan et al, 2007;Rosati et al, 2017;Smith et al, 2018;Tweneboah-Kodua et al, 2018;Yayla & Hu, 2011). This statistical practise advocates that an unanticipated event is probable to influence (increase or decrease) the script price resulting an abnormal returns on script prices (MacKinlay, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the special influence of a range of incidents, from corporate purchases to joint venture establishment to CEO progressions the method of 'event study' has been engaged comprehensively in the accounting, finance and information security literature (Bose & Leung, 2013;Cavusoglu et al, 2004;Hovav et al, 2017;Kannan et al, 2007;Rosati et al, 2017;Smith et al, 2018;Tweneboah-Kodua et al, 2018;Yayla & Hu, 2011). This statistical practise advocates that an unanticipated event is probable to influence (increase or decrease) the script price resulting an abnormal returns on script prices (MacKinlay, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…While intangible costs are difficult to estimate, such as loss of trust, reputation, and confidence by business stakeholders for future transactions. Underpinned by the Efficient Market Hypothesis in its semi-strong form (Fama, 1991;Fama et al, 1969;Malkiel & Fama, 1970) researches have tried to examine the impact of IS breach announcements on stock prices for effected firms (Berkman et al, 2018;Bianchi & Tosun, 2018;Campbell et al, 2003;Cavusoglu et al, 2004;Ettredge & Richardson, 2001;Hovav & D'Arcy, 2004;Kannan et al, 2007;Malhotra & Kubowicz Malhotra, 2011;Pirounias et al, 2014;Sangvinatsos, 2017;Sinanaj & Muntermann, 2013;Smith et al, 2018;Tweneboah-Kodua et al, 2018). Most of these studies have concluded a negative impact on stock price by considering the effect of un-systematic risk factors surrounding the breach such as factors specific to that type of attack (Arcuri et al, 2017;Bose & Leung, 2014;Hovav & D'Arcy, 2003), type of firm (Cavusoglu et al, 2004;Goel & Shawky, 2009;Rosati et al, 2017) and type of industry (Pirounias et al, 2014;Yayla & Hu, 2011) as shown in Figure 01.…”
Section: Introductionmentioning
confidence: 99%
“…Siber suç genellikle yalnızca çalınan varlıklara ve iş kaybına neden olmakla kalmaz, aynı zamanda bir şirketin itibarına da zarar vermekte, bu da şirketin borsa değerini etkileyebilmektedir. Bu durum şirket yöneticileri, finansal analistler, yatırımcılar ve alacaklılar yönünden ciddi bir endişe kaynağıdır (Smith et. al., 2019).…”
Section: Yöntem Ve Veri̇ Seti̇unclassified
“…The results are similar as in the An & Kim (2018) stated that the companies most exposed to cyber-attacks were technology, finance, e-commerce, and telecommunications companies. Smith et al, (2019) show that there is a negative but not significant impact on the market value of stock prices after cybercrime is announced. So, they concluded that the average share prices of companies fell in the days after the cybercrime news.…”
mentioning
confidence: 92%
See 1 more Smart Citation